Survival and risk factors associated with mortality in people living with HIV from 2005 to 2018 in Nanjing, China - Zhu, Zhengping; Xu, Yuanyuan; Wu, Sushu; Li, Xin; Shi, Hongjie; Dong, Xiaoxiao; Xu, Wenjiong (Frontiers in Public Health, 2022)
Objectives To evaluate survival patterns and identify factors related to death among people living with HIV in Nanjing, China. Methods We conducted a retrospective analysis of people living with HIV (PLHIV) registered to the national HIV/AIDS comprehensive management information system from 2005 to 2018. Life table, the Kaplan-Meier and Cox hazard proportional regression were used to calculate the survival time and its associated factors. Results Of the total 4235 PLHIV, 7.51% had died of AIDS-related disease (2.01/100 person years). The median survival time of PLHIV was 11.78 (95%CI：11.64 11.93) years. The cumulative proportion surviving at the end of interval was 95.17% over 1st year, 94.03% over 2nd year, 91.82% over 5th year and 85.42% over 10th year, respectively. Characteristics associated with greater risk of death included unaccepted Antiretroviral Treatment (HR=16.24, 95%CI：11.89 22.19), baseline CD4+ T lymphocyte cell count <200/μL (HR=0.40, 95%CI：0.27 0.58 for 200 349/μL; HR=0.29，95%CI：0.19 0.43 for 350 499/μL; HR=0.24, 95%CI: 0.15 0.37 for ≥500/μL), outpatient (HR=1.56, 95%CI: 1.11 2.17), inpatient (HR=1.64, 95%CI: 1.09 2.45), older age (HR =5.03, 95%CI: 2.03 12.48 for 25 49 years old; HR=9.48, 95%CI: 3.73 24.10 for ≥50 years old) and lower education background patients (HR=1.73, 95%CI: 1.10 2.74 for senior high school; HR=3.40, 95%CI: 2.26 5.11 for junior high school). Conclusion We found that unaccepted ART, lower basic CD4+ T lymphocyte cell count, older age and lower educated increase the risk for AIDS related death among PLHIV. Targeted intervention on test motivation and treatment initiation should be strengthened in Nanjing.